Online Interactive Learning Media: Unlocking Language Learning Motivation - Y Yusnimar; Ismaniar Isa; Ernawati Br Surbakti (Universitas Teuku Umar, 2026)
Online learning media development somehow forces lecturers who teach in higher education to catch up with the latest learning media, which benefits to learning motivation and performance of the students. Finding online resources by google search would be more beneficial for the students when they get enough guidance or assistance from the lecturer. This study was to investigate whether the use of Mentimeter interactive learning website would boost language learning motivation and performance of the students. The participants were two groups of students, the total respondents were 42 first year civil engineering students. Pre-test and post-test were given to assess students’ ability and motivation in learning specialized English words used in civil engineering field before and after the learning strategy implemented. In the post test, students showed the improvement of learning motivation and ability compared to the result in the pre-test. It could be seen from the average scores the students achieved by group 1 and group 2 in the post test were 84.3 and 84.2, respectively. The scores were much higher compared to the average score gotten by the group 1 and group 2 in the pre-test, which were 55 and 54.7, respectively. It could be summed up that Mentimeter learning website could boost English learning motivation which in turn increased learning performance in learning technical English vocabulary for civil engineering students. Once students highly motivated the performance and ability also increase sharply.